2020
DOI: 10.1007/s42978-020-00081-2
|View full text |Cite
|
Sign up to set email alerts
|

Speed of Thought and Speed of Feet: Examining Perceptual-Cognitive Expertise and Physical Performance in an English Football Academy

Abstract: The world’s greatest professional football players are able to execute effective tactical decisions as well as fulfil various physical demands. However, the degree to which both are associated with greater potential in a football academy is unknown. Therefore, the aim of this study was to investigate decision-making skill and physical performance as contributing factors to coach potential rankings in an English football academy. Ninety-eight outfield academy players (Foundation Development Phase [FDP] under-9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…A perceptual-cognitive video simulation test was used to examine the participants' decision-making skill based on a combination of tactical situations, which have been shown to be valid and reliable measures for PCE research in several sport environments (e.g., Kelly et al, 2020). Fifteen video clips were carefully chosen from live rugby match footage, filmed from different elevated angles to provide a wide-range view of the pitch.…”
Section: Methodsmentioning
confidence: 99%
“…A perceptual-cognitive video simulation test was used to examine the participants' decision-making skill based on a combination of tactical situations, which have been shown to be valid and reliable measures for PCE research in several sport environments (e.g., Kelly et al, 2020). Fifteen video clips were carefully chosen from live rugby match footage, filmed from different elevated angles to provide a wide-range view of the pitch.…”
Section: Methodsmentioning
confidence: 99%
“…A perceptual-cognitive video simulation test was used to examine the participants' decision-making skills based on a combination of tactical situations, which have been used in RU literature [1] and demonstrated to produce valid and reliable measures for PCE research in several sport environments, e.g., [44]. Game situations of fifteen video clips were chosen from live rugby match footage, filmed from different elevated angles to provide a wide-range view of the pitch.…”
Section: Perceptual-cognitive Expertise (Pce)mentioning
confidence: 99%
“…Moreover, it is important to mention that present results only reflect the status of a single Premiership RU academy, and thus it is possible that this is not representative of other environments in RU. However, other studies surrounding TD in RU [16] and football [44] adopted similar methodological procedures when analysing academies of professional clubs. Furthermore, some data were collected retrospectively (e.g., game exposure, peer-led play, and coach-led training), and therefore recall bias may have influenced findings.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…A training study by Morris et al, spanning a large population of youth football players in different maturity categories, found that resisted sprint training only maintained strength, sprint and jump performance, rather than improving those qualities [7]. Practitioners may need to find alternative methods to develop those qualities as Kelly and colleagues show that young soccer players ranked with higher potential by their coaches sprint faster and jump higher than their lower ranked teammates [4]. Kelly et al also show that higher ranked players display superior decision-making and perceptual-cognitive skills, reinforcing the need for a multidisciplinary approach to talent development [4].…”
mentioning
confidence: 99%
“…Practitioners may need to find alternative methods to develop those qualities as Kelly and colleagues show that young soccer players ranked with higher potential by their coaches sprint faster and jump higher than their lower ranked teammates [4]. Kelly et al also show that higher ranked players display superior decision-making and perceptual-cognitive skills, reinforcing the need for a multidisciplinary approach to talent development [4]. For practitioners wanting to use jump training with young female athletes, Gillen et al examine a number of jump conditions to describe the influence of eccentric pre-loading on kinetic outcomes while also examining the influence of size and maturity [3].…”
mentioning
confidence: 99%